Swimming to suburbia and other essays - Hodgetts, Craig 1937- (ORO Editions, 2018)
Widely known for his award-winning design work, the Los Angeles-based architect Craig Hodgetts has distinguished himself as one of the key voices of his generation through trenchant commentary and visionary speculation on architecture and design. This volume gathers an array of theoretical polemics on buildings and cities, critical assessments of major projects and personalities, and other writings that showcase Hodgetts' unique position as both a central figure in the discipline of architecture and a tireless advocate of technological opportunities developed at the fringes of the field. Contextualized with a critical introduction by historian Todd Gannon and illustrated with rare materials from Hodgetts' archive, this collection cuts a revealing cross-section through a turbulent period during which architecture's confidence in the Modernist project was shaken, its intellectual energies redirected, and its cultural agenda re-imagined in the face of environmental challenges, technological opportunities, lingering disciplinary traditions, and revolutionary new ideas
Edited and with an introduction and commentary by Todd Gannon
Keywords: Geschichte 1950-2018; Architektur; Innenarchitektur; Design; USA; Architecture, Modern; Aufsatzsammlung